2017
DOI: 10.5144/0256-4947.2017.326
|View full text |Cite
|
Sign up to set email alerts
|

Perception of hospital accreditation among health professionals in Saudi Arabia

Abstract: BACKGROUNDHospital accreditation assesses hospital performance against explicit standards. Studies of the efficacy of accreditation are limited, but suggest that Joint Commission International (JCI) accreditation is efficient in improving the safety and quality of care in accredited hospitals.OBJECTIVESThis study aimed to assess the perceptions of health professionals on the impact of JCI accreditation and implementation of change towards the delivery of quality patient care.DESIGNCross-sectional survey.SETTIN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
48
0
8

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(60 citation statements)
references
References 9 publications
4
48
0
8
Order By: Relevance
“…The findings of a study carried out with 901 health professionals from Saudi Arabia corroborate with the results of this study, who referred to Accreditation as responsible for direct improvements in the work process, in face of their normative requirements 6 . On the other hand, another investigation carried out with 1312 nurses from Iran testifies that, despite bringing robustness to the work process, the impact of Accreditation on the quality of concrete results can not yet be taken as absolute truth 22 .…”
Section: Discussionsupporting
confidence: 81%
“…The findings of a study carried out with 901 health professionals from Saudi Arabia corroborate with the results of this study, who referred to Accreditation as responsible for direct improvements in the work process, in face of their normative requirements 6 . On the other hand, another investigation carried out with 1312 nurses from Iran testifies that, despite bringing robustness to the work process, the impact of Accreditation on the quality of concrete results can not yet be taken as absolute truth 22 .…”
Section: Discussionsupporting
confidence: 81%
“…The lack of knowledge of standard treatment guidelines and poor enforcement efforts foster inappropriate antimicrobial use and increase the prevalence of AMR [15]. A qualitative study by Algahtani et al [16] found that accreditation [17] improved the process and implementation of change in hospitals and, in turn, improved the delivery of healthcare services and quality of care.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the "evident" relationship between accreditation and patient safety, since the second is one of the central focuses of the quality management system in question, studies which enable better/greater knowledge about the effects of accreditation in different aspects have been recommended by recently published research, and not only in Brazil (7)(8)10,(13)(14)(15) , which means investigating the potentials of this quality certification process, which undoubtedly includes patient safety, still denotes novelty and mainly necessity. Furthermore, even if this gap in knowledge exists, one is based on the empirical principle that there is some relationship, whether positive or not, between the researched phenomena.…”
Section: Introductionmentioning
confidence: 99%